The collected stories - Price, Reynolds 1933-2011 (Atheneum, 1993)
In his introduction, Mr. Price explains how, after the publication of his first two collections, he wrote no new stories for almost twenty years. "But once I needed - for unknown reasons in a new and radically altered life - to return to the story, it opened before me like a new chance...A collection like this then," he adds, "...will show a writer's pre-occupations in ways the novel severely rations (novels are partly made for that purpose - the release from self, long flights through the Other). John Keats's assertion that 'the excellence of every Art is its intensity' has served as a license and standard for me. From the start my stories were driven by heat - passion and mystery, often passion for the mystery I've found in particular rooms and spaces and the people they threaten or shelter - and my general aim is the transfer of a spell of keen witness, perceived by the reader as warranted in character and act."
Keywords: Geschichte 1900-2000; Alltag, Brauchtum; Short stories; Short stories, American.; USA; North Carolina -- Social life and customs -- Fiction; United States -- Social life and customs -- 20th century -- Fiction